1968
DOI: 10.1104/pp.43.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis in Abscission: The Distinctiveness of the Abscission Zone and its Response to Gibberellic Acid and Indoleacetic Acid

Abstract: A bstract. Abscission zone tissue of citrus was shown to have a higher rate of protein synthesis than tissue distal or proximal to it. based on the incorporation of leucine-1-14C. The proximal tissue had the slowest rate of protein synthesis. As the tissue approached abscission, the rate of synthesis in the abscission zone decreased and the differences in rate of protein synthesis between the 3 zones almost disappeared. IAA, which delayed abscission, maintained the protein synthesis gradient between the abscis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1969
1969
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…This was evident from the fact that the petiole section distal to the separation layer remained on top of the callus (Altman and Goren 1971). The present system differs from previously reported systems by the general decrease in protein synthesis which occurs during the inductive stage of callus formation (first 5 days from excision), instead of the usual increase in protein synthesis which is characteristic of the inductive period of abscission (Abeles and Holm 1967, Abeles 1968, Lewis and Bakhshi 1968, Osborne 1968). These results are in accordance with the decrease in protein synthesis in the abscission zone of young citrus fruits during the first stages of abscission (Goren et al 1974).…”
Section: Discussioncontrasting
confidence: 85%
“…This was evident from the fact that the petiole section distal to the separation layer remained on top of the callus (Altman and Goren 1971). The present system differs from previously reported systems by the general decrease in protein synthesis which occurs during the inductive stage of callus formation (first 5 days from excision), instead of the usual increase in protein synthesis which is characteristic of the inductive period of abscission (Abeles and Holm 1967, Abeles 1968, Lewis and Bakhshi 1968, Osborne 1968). These results are in accordance with the decrease in protein synthesis in the abscission zone of young citrus fruits during the first stages of abscission (Goren et al 1974).…”
Section: Discussioncontrasting
confidence: 85%
“…The fact that CHI was found to inhibit cellulase activity in the presence of ethylene or in the absence of the hormone is not surprising, since abscission is known to be related to RNA and to protein synthesis (4,14,17,22,30). Results presented in talble II show that the RNA analogue 2-thio-uracil (2-TU), significantly inhibited abscission and cellulase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Lewis (16,17) studied the effects of GA8 and IAA on the albscission of citrus leaf explants, and showed that the acceleration of abscission by GA3 is probably due to stimulation of protein synthesis, while IAA maintains the rate of protein synthesis in the cells of the abscission zone. These findings are compatible with the results reported by Abeles (4), who showed that the abscission process is characterized by "de novo" synthesis of RNA and protein.…”
mentioning
confidence: 99%
“…al, 1988). Likewise, auxin seems to maintain existing rates of protein synthesis in abscission zones of citrus (Lewis and Bakhshi 1968).…”
Section: Discussionmentioning
confidence: 99%